An Analysis of Speech Act on Racist Case of Philadelphia Students Posted on CNN Instagram Account - Julianti, Eka Tri; La sunra, La sunra; Fitriyani, Fitriyani (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
Social media users interact through photos or videos, and there are many things we can do, especially Instagram. We can find out important information by reading the news provided on the Instagram accounts of news media. The above issues had been investigated by some scholars, (Tutuarima et al, 2018) which has also conducted research on the issue of an analysis of speech act used in london has fallen movie. The researcher presents something new in the form of identification of speech acts uttered by readers. Where the researcher's data is in the form of comments which classified according to the type of utterance and how the researcher can present responses from readers who comment on published utterances. The aim of this research is to analyze the types of speech acts used by readers in the comments column of CNN's Instagram account in order to find out the use of each type of speech. The researcher used the theory of John L. Austin (1967) to explain speech acts and their types and the responses given by readers and analyze the responses of readers. Qualitative descriptive research methods were used in this research, and used a pragmatics approach. The researcher found for locutionary acts 21 utterances . For illocutionary acts, the researcher found 39 utterances and for perlocutionary acts, the researcher found 2 utterances which were included in perlocutionary acts. The researcher concluded that readers mostly used illocutionary acts in providing comments because readers paid attention and used clear communicative purposes in making comments such as asking questions, giving advice or ordering and expressing their feelings. The researcher also concluded that readers responded by giving likes to other readers' utterances or by providing support, or disagreeing and neutral opinions by also providing comments on the post.Keywords: speech act, instagram, readers, comments, social media